An Evaluation of Production Versus Error-Recognition Techniques for Teaching APA-Style Citations and References. (October 2019) - Boysen, Guy A.
American Psychological Association (APA)-style writing is an essential part of the undergraduate psychology curriculum. However, little is known about the effectiveness of specific techniques for instructing students on how to format APA-style citations and references. The current research compared the effectiveness of having students ( N = 76) produce versus recognize errors in APA-style citations and references. Production of materials led to significantly better performance on both an immediate quiz and a later test. Student evaluations ( N = 43) of the activities showed that they elicited similar enjoyment and effort, but most students preferred the error-recognition activity despite indicating that the production activity would lead to more learning. These results indicate that initial instruction of APA style should emphasize the production of correctly formatted APA-style materials.